Twenty‐eight‐year review of childhood renal diseases from renal biopsy data: A single centre in China. Issue 12 (December 2016) - Jiang, Mengjie; Xiao, Zizheng; Rong, Liping; Xu, Yuanyuan; Chen, Lizhi; Mo, Ying; Sun, Liangzhong; Sun, Wei; Jiang, Xiaoyun
Abstract: Aim: The aim of the present study was to investigate the clinicopathologic characteristics of biopsy‐proven childhood renal diseases and to compare the trends and changes during two different time intervals between 1984 and 2011 at the First Affiliated Hospital of Sun Yat‐sen University in China. Methods: We retrospectively analyzed kidney biopsy data from children with renal diseases and compared the data during two time intervals, namely 1984–1997 and 1998–2011. Results: A total of 1313 children were enrolled in the present study. There were 921 children with primary glomerular disease (PGD) and 312 children with secondary glomerular disease (SGD), accounting for 70.1% and 23.8% of participants, respectively. The major clinical manifestation of PGD was nephrotic syndrome (NS), which accounted for 31.2% of cases, while the main aetiology of SGD was lupus nephritis (40.7%). The main biopsy patterns of PGD were IgA nephritis (27.6%), minimal change disease (24.0%), and mesangial proliferative glomerulonephritis (16.9%). PGD was the major class of disease in both time intervals, but the ratio of PGD decreased over time, while the ratio of SGD and other glomerular diseases increased. PGD was also the major class of disease in each age group; however, the incidence of PGD decreased with increasing age. Conclusion: The incidence patterns of paediatric renal diseases changed over the 28‐year period of this study. Our results show that different renal diseases characterize different age intervals. Furthermore, there are several associations between clinical presentation and biopsy features in childhood renal disease. Summary At a Glance: This manuscript investigated the clinicopathological characteristics of biopsy‐proven childhood disease and observed that the incidence patterns of pediatric renal disease had changed over the 28‐year period. The results found in this study will provide useful information in the field of pediatric nephrology.